Impendence of Ethos and Incandescence in K.N. Daruwalla’s Poetry: Exploring the Interplay of Nature and Human Passions in K.N. Daruwalla’s Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Keki Nasserwanji Daruwalla is surely one of the significant voices in Indo-Anglian poetry. He won the Sahitya Akademi award and he writes with evident Indian components in his stanzas, particularly in his utilization of the landscapes, nature and human passions. His reasonable vision of human life and his own perception are his subjects. His own perceptions are not completely certainties; they are amalgam of myth and reality. Nature and landscapes possess a fundamental place among the subjects of Daruwalla’s Parnassus. He has written numerous poems on places with most powerful and vivid symbolism. Through his poems, he draws out the present reality of nature, and states how the cutting edge man has controlled it. In his poetry, he interknits both the nature and human passions. The images he utilizes are normal yet the thoughts, which the images contain, are exceptionally scholarly with an expansive sense.